2014
DOI: 10.5430/jnep.v4n11p8
|View full text |Cite
|
Sign up to set email alerts
|

How is peer-teaching perceived by first year paramedic students? Results from three years

Abstract: Background: Peer Assisted Learning (PAL) can create a cooperative learning environment, providing benefits to all students involved. While there is a large pool of research exploring PAL amongst medical students it is worth considering the use of PAL amongst students of different health disciplines. The objective of this study was to examine the perceptions of first year paramedic peer learners being taught by peer teachers over a three-year period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 30 publications
(64 reference statements)
5
10
0
Order By: Relevance
“…Based on the results and discussions on reviewed studies, this study have found that Singh, Scicluna, and Abdolalizadeh all had strongly implied the benefit of peer mentoring program in developing students' communication skills. Supported by previous study with similar result [14]- [17], Singh et al found in their studies that mentors developed improvement in communication skills as a result of mentoring activities, as the previous study [9]. Scicluna et al found that teaching their juniors improved mentors' communication skills.…”
Section: Good Communication Skillsmentioning
confidence: 53%
“…Based on the results and discussions on reviewed studies, this study have found that Singh, Scicluna, and Abdolalizadeh all had strongly implied the benefit of peer mentoring program in developing students' communication skills. Supported by previous study with similar result [14]- [17], Singh et al found in their studies that mentors developed improvement in communication skills as a result of mentoring activities, as the previous study [9]. Scicluna et al found that teaching their juniors improved mentors' communication skills.…”
Section: Good Communication Skillsmentioning
confidence: 53%
“…This may be because the peer teaching provide an opportunity to the student to explore ideas without fear of embarrassing themselves in front of their lecturer. This result came in line with Williams etal., (2014) (31) who revealed that, social interaction and collaboration was increased in peer teaching group more than traditional teaching group. At the same line, Cho etal., (2015) (27) reported that, all student in peer teaching group were became social interactive with other students, more friendly, and learned collaboratively.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in agreement with Cho etal., (2015) (27) who showed that, peer teaching may be an effective method for training students to perform CPR . Similarly, Williams etal., (2014) (31) who concluded that, peer teaching could be a useful adjunct in clinical skills training. In contrary, previous study by Hughes etal., (2010) (32) failed to show the supremacy of peers teaching in CPR training compared with traditional approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The first part identified student demographics; the second part identified student attitudes towards and experiences of paramedicine-specific NPT. The questionnaire utilised an adapted version of the Williams, Wallis and McKenna (2014) peer-assisted learning (PAL) student study.…”
Section: Instrumentationmentioning
confidence: 99%
“…The benefits of introducing such programs into health and medical education programs are well documented, however there is a paucity of literature relating to NPT programs in paramedicine education (Hogan et al, 2017;Williams, Wallis, & McKenna, 2014). In the Griffith University paramedicine program, a series of successful NPT years have been facilitated in both first-and second-year curricula since the program's inception 5 years ago.…”
Section: Introductionmentioning
confidence: 99%